2013 16th International Conference on Advanced Robotics (ICAR) 2013
DOI: 10.1109/icar.2013.6766586
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically programmable bend radius for fiber-reinforced soft actuators

Abstract: Abstract-Established design and fabrication guidelines exist for achieving a variety of motions with soft actuators such as bending, contraction, extension, and twisting. These guidelines typically involve multi-step molding of composite materials (elastomers, paper, fiber, etc.) along with specially designed geometry. In this paper we present the design and fabrication of a robust, fiber-reinforced soft bending actuator where its bend radius and bending axis can be mechanically-programed with a flexible, sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
155
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 250 publications
(159 citation statements)
references
References 10 publications
2
155
1
1
Order By: Relevance
“…To realize actuators capable of replicating complex motions, we use segments consisting of a cylindrical elastomeric tube surrounded by fibers arranged in a helical pattern at a characteristic fiber angle α ( Fig. 2A) (23,24), because it has been shown that by varying the fiber angle and materials used, these segments can be easily tuned to achieve a wide range of motions (17)(18)(19)(20)(21). When the elastomeric tube is of uniform stiffness, the segment undergoes some combination of Significance Fluid-powered elastomeric soft robots have been shown to be able to generate complex output motion using a simple control input such as pressurization of a working fluid.…”
Section: Analytical Modeling Of Actuator Segmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…To realize actuators capable of replicating complex motions, we use segments consisting of a cylindrical elastomeric tube surrounded by fibers arranged in a helical pattern at a characteristic fiber angle α ( Fig. 2A) (23,24), because it has been shown that by varying the fiber angle and materials used, these segments can be easily tuned to achieve a wide range of motions (17)(18)(19)(20)(21). When the elastomeric tube is of uniform stiffness, the segment undergoes some combination of Significance Fluid-powered elastomeric soft robots have been shown to be able to generate complex output motion using a simple control input such as pressurization of a working fluid.…”
Section: Analytical Modeling Of Actuator Segmentsmentioning
confidence: 99%
“…Here, we focus on fiber-reinforced actuators (17)(18)(19)(20)(21), and given a particular trajectory, we find the optimal design parameters for an actuator that will replicate that trajectory upon pressurization. To achieve this goal, we first use a nonlinear elasticity approach to derive analytical models that provide a relationship between the actuator design parameters (geometry and material properties) and the actuator deformation as a function of pressure for each motion type of interest (extending, expanding, twisting, and bending).…”
mentioning
confidence: 99%
“…Position vector of effectors when λ a = 0. δ to develop effective methods for the design and analysis of soft robots. New design methodologies are proposed using promising soft actuator technologies [4], [5]. However, the accuracy and efficiency of soft robots is still limited by the difficulties of modeling and control of deformable systems that have, theoretically, an infinite number of degrees of freedom.…”
Section: Visual Servoing Control Of Soft Robots Based On Finite Elemementioning
confidence: 99%
“…Our modeling and analysis work builds on the earlier papers Majidi et al (2012Majidi et al ( , 2013a; Zhou et al (2015) While we do not discuss the precise mechanism by which the intrinsic curvature is changed, there has been an increased interest in the development of mechanisms for changing κ 0 in components of soft robots. The interested reader is referred to Galloway et al (2013); Shepherd et al (2013); Suzumori et al (2007); Takashima et al (2011);Wakimoto et al (2009) for examples of these mechanisms. Also, in order to make the theoretical model more tractable for analysis, we only examine gripping mechanisms that involve point contact with an object.…”
Section: Introductionmentioning
confidence: 99%
“…This is most pronounced in grippers that conform to an object and make contact along a finite length, as is demonstrated in Figures 1(b)&(c). In the case of angular objects (i.e., with straight edges), such "shape matching" is enhanced by adding a conformal sleeve to the actuator, which restricts bending to predefined joints (Galloway et al, 2013). Nonetheless, even in the case of soft grippers that only make point contact with an object, such as those in Figures 1(a)&(d), bending can have a dramatic influence on control, contact force, and load bearing capability.…”
Section: Introductionmentioning
confidence: 99%